The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3889/oamjms.2021.6457
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with PEGylated Hyaluronic Acid Fillers: A 3-year Retrospective Study

Abstract: BACKGROUND: Hyaluronic acid fillers are the most used worldwide, thanks to the high biocompatibility and safety profile of HA and it is also the only substance that can be “dissolved” due to the hyaluronidase effect. AIM: A retrospective clinical evaluation of the outcomes following PEG cross-linked HA-based filler injection was performed. METHODS: Data were collected from December 2017 to June 2020. A total of 65 patients (12 M, 53 F), age ranging 28–62 year’s old (mean age 42.3), were treated. Exclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Results concerning the ability of PEGylated hyaluronic acid gel to modulate human immune functions suggest that they carry a very low risk of immune-mediated adverse effects, particularly granulomatous reactions and associated cellulitic processes [ 15 ]. In this study, we observed a significant decrease in the overall local inflammatory infiltrate, which reached a frequency significantly lower than before the administration of Neauvia PEGylated fillers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Results concerning the ability of PEGylated hyaluronic acid gel to modulate human immune functions suggest that they carry a very low risk of immune-mediated adverse effects, particularly granulomatous reactions and associated cellulitic processes [ 15 ]. In this study, we observed a significant decrease in the overall local inflammatory infiltrate, which reached a frequency significantly lower than before the administration of Neauvia PEGylated fillers.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in the number of antigen-recognizing T lymphocytes (CD4+), cytotoxic T lymphocytes (CD8+), and CD68+ innate immune cells suggests that PEGylated hyaluronic acid gel fillers are not recognized as a foreign body. Cross-linking agents in PEGylated hyaluronic acid gel fillers might have contributed to the high biocompatibility of the incorporated product, which reduces the risk of adverse events related to the immune response, such as the formation of granulomas [ 15 ]. An important feature of polyethylene glycol and hyaluronic acid is that they create a matrix with a scaffold structure, a sort of 3D molecular scaffold, that has better integration with the host tissue, gaining a long-lasting effect and better resistance to thermal and mechanical stress.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No adverse events were observed apart from minimal bruising and swelling, which were mostly resolved within 24h of injection. PEGDE-HAs are a relatively recent introduction to the esthetic field and published clinical data are only just starting to appear [14]. A 3-year retrospective study of clinical experience with PEGDE-HAs for a range of treatment indications reported long-term results with no safety concerns, including no nodules, granulomas, or foreign body reactions [14].…”
Section: Discussionmentioning
confidence: 99%